2016
DOI: 10.1016/j.maturitas.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Acute ascorbic acid infusion increases left ventricular diastolic function in postmenopausal women

Abstract: Objectives We tested the hypothesis that oxidative stress contributes to reductions in left ventricular diastolic function in estrogen-deficient postmenopausal women, related in part to reduced nitric oxide (NO) bioavailability. Study design LV diastolic function – recorded using transthoracic echocardiography and determined as the peak early (E) to late (A) mitral inflow velocity ratio and the E to peak early (e’) mitral annular velocity ratio – and brachial artery flow mediated dilation (FMD), a biomarker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…In cardiac myocytes, a decrease in nitric oxide disrupts calcium kinetics [ 33 ] and impairs cardiac relaxation [ 34 ]. Previous investigations have also demonstrated improved cardiac function with acute [ 16 ] and chronic [ 13 15 ] antioxidant therapy administration. Thus, it is possible that the beneficial effect of vitamin C on diastolic function in this study was through modulation of oxidant burden.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cardiac myocytes, a decrease in nitric oxide disrupts calcium kinetics [ 33 ] and impairs cardiac relaxation [ 34 ]. Previous investigations have also demonstrated improved cardiac function with acute [ 16 ] and chronic [ 13 15 ] antioxidant therapy administration. Thus, it is possible that the beneficial effect of vitamin C on diastolic function in this study was through modulation of oxidant burden.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular function is a primary contributor to exercise capacity and it is impaired in people with T2D, providing a logical potential cause of the impaired cardiorespiratory fitness of T2D. In previous studies, supplementation with antioxidants has augmented cardiac function [ 13 16 ] and vasodilation [ 17 19 ] which may impact tissue oxygen delivery in both central and peripheral circulations and affect the utilization of oxygen during exercise. However, to date we have not determined the isolated effects of cardiovascular function, per se, on cardiorespiratory fitness in persons with T2D.…”
Section: Introductionmentioning
confidence: 99%
“…A few of the included trials reported effects of vitamin C on measures of cardiac physiology other than LVEF and found that vitamin C increased cardiac perfusion after PCI (43,44), improved diastolic function in an exercise test (52), and increased systolic myocardial velocity during hyperoxia (48). In addition to the included trials, a few other trials have reported that vitamin C had an effect on the mechanical function of the heart (76)(77)(78)(79).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in physiological laboratories vitamin C administration has shown a wide range of effects that are relevant to the cardiac system, such as increasing coronary artery diameter [ 45 49 ], coronary flow [ 195 201 ], improving effects of inotropic agents [ 202 – 206 ], increasing baroreflex sensitivity [ 207 210 ], alleviating postural tachycardia [ 211 ], increasing left ventricular diastolic function [ 212 ] and preventing nitrate tolerance [ 213 215 ]. Most of these physiological studies were short.…”
Section: Discussionmentioning
confidence: 99%